Barriers to effective corporate governance principles in state-owned enterprises in Zimbabwe - Job Dubihlela; Henry Mukono (Jurnal Akuntansi & Auditing Indonesia, 2022)
The purpose of this article is to discuss the barriers to effective corporate governance principles in state-owned enterprises (SOEs) in Zimbabwe in order to have an influence on policy debates. This study used a qualitative research approach, and a case study research design was followed, in order to attain the objective of the research. Semi-structured interviews were carried to get the views of the respondents on barriers to effective corporate governance principles in SOEs in Zimbabwe. Respondents chosen were members of the audit committees (ACs), permanent secretaries (PSs), chief executive officers (CEOs), senior managers (SMs), board of directors (BoDs) and chief audit executives (CAEs). Respondents were chosen due to their ability to act on the study’s findings and recommendations. Data was analysed using Atlas.ti version 8. The study revealed that there are cases of poor and mis-governance in SOEs in Zimbabwe. Egregious cases include non-adherence to corporate governance rules and laws, degenerating against the Public Finance Management Act, [Chapter 22:19] as well as paying ignore in the submission of the financial statements which are audited. The article therefore, recommends that for an emerging country like Zimbabwe to enjoy the advantages of effective corporate governance principles, reviewing the legislations which are currently there as well as strengthening the enforcement strategies of the regulatory institutions is of paramount importance. The findings are limited to a Zimbabwean case study alone. Be that as it may, great lessons can be drawn for other developing economies from the case study. Apart from classifying cases of poor or mal-governance in SOEs in Zimbabwe, the article gives recommendations for policy in-order to improve corporate governance in SOEs in Zimbabwe. There is a dearth of study on barriers to effective corporate governance principles in SOEs in Zimbabwe; therefore, there is a gap in the literature. Hence, the paper makes an original contribution to the literature. Finally, the paper advocates fruitful avenues for future research on the future of corporate governance.